Outcomes between Conventional versus Minimal Invasive Dynamic Hip Screw in Fixation of Intertrochanteric Fracture of Femur - Asif Ali Shaikh, Saifullah Soomro, Muhammad Shuaib, Ghulam Sarwar, Mushtaque Ahmed Shaikh, Saqib, Zamir Ahmed Soomro (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the outcomes between conventional versus Minimal invasive dynamic hip screw in fixation of intertrochanteric fracture of femur Materials and Methods: This is randomized control trial, conducted at Department of Orthopedic Surgery, Shaheed Mohtarma Benazir Bhutto Medical University (SMBBMU), Larkana, Pakistan from November 9, 2020 to May 8, 2021. All patients who fulfilled the inclusion criteria and visited to SMBBMU, Larkana were included in the study. After taken Informed consent, exclusion criteria were followed strictly. Results: Mean±SD of age in MIDHS group was 54.6±9.5 and CONDHS group was 55.8±9.8 years. Mean ± Standard Deviation of blood loss & duration of surgery was noted as (51.3±16.4 v/s 145.1±26.4; [P=0.0001] ml) and (54.5±11.4 v/s 76.2±17.7; [P=0.0001] mins) among MIDHS and CONDHS groups respectively. While duration of hospital stay was noted as 3.6±2.2 and 8.1±4.9 in MIDHS v/s CONDHS groups respectively with a highly significant difference i.e., (P=0.0001). Conclusion: It is to be concluded that highly significant difference was noted in comparison of outcomes between conventional v/s Minimally invasive dynamic hip screw for the fixation of intertrochanteric fractures of femur. Keywords: Conventional, Femur, Intertrochanteric Fractures, Hip Screw, Outcomes